Revegetation analysis of Freeport Indonesia mine reclamation area using remote sensing technology - Rahmadhani, Rizky; Manessa, Masita Dwi Mandini; Supriatna, Supriatna; Setiabudi, Firman; Amiruddin, Amiruddin (Brawijaya University, 2026)
One of the largest mining companies in the world is PT Freeport Indonesia, located in Mimika Regency, Papua. In its mining operations, PT Freeport Indonesia faces a number of environmental problems, one of which is the change of vegetated land into barren land. Environmental damage caused by mining activities can be restored through reclamation activities and monitored using remote sensing technology. In this study, the remote sensing images used were Sentinel-2 images collected from 2016 to 2023 to obtain the distribution of vegetation cover index and vegetation greenness in the Grasberg Reclamation Area. The variables used to analyze changes in vegetation cover during the revegetation process in the Grasberg Reclamation Area are Normalized Difference Vegetation Index (NDVI), vegetation type, reclamation year, elevation, slope, and slope direction. This study shows that as the reclamation time increases, the area covered by vegetation with medium and high greenness levels increases. Changes in vegetation cover in the Grasberg Reclamation Area show an increasing trend covering 379.66 hectares or 98.71% of the total reclamation area and the others show a decreasing trend. Meanwhile, changes in vegetation cover in the Grasberg Reclamation Area based on the results of the correlation test are influenced by topographic conditions. The elevation of the area does not show a strong influence on vegetation cover but steep slopes will trigger a low level of vegetation cover greenness and vice versa. The vegetation on the east-facing slope has a high level of greenery because it gets enough sunlight. Monitoring changes in vegetation cover in ex-mining reclamation areas is very useful for land management policies in mining areas and reclamation planning.